Haematophagous parasites of some fish species in the Lower Irtysh - Е. L. Liberman (Российский паразитологический журнал, 2021)
The purpose of the research is study of four fish species infected with haematophagous parasites in the rivers of the Lower Irtysh basin. Materials and methods. The work was performed in the rivers of the Lower Irtysh basin in 2017–2020. A total of 390 fish of different sex and age were examined including 47 roach (Rutilus rutilus lacustris, (Pallas)), 41 ide (Leuciscus idus, (Linnaeus, 1758)), 47 pike (Esox lucius, (Linnaeus, 1758)) and 255 Siberian sterlet (Acipenser ruthenus marsiglii (Brandt, 1833)). We took blood from the tail artery, and examined its fresh drop under a microscope, and prepared a thin smear, then dried it in the air and fixed in a mixture of 70% ethyl alcohol and diethyl ether (1 : 1) for 30 minutes. The fixed smears were dried in the air at room temperature and stained with azure and eosin at a dilution of 1 : 10 for 40 minutes. We identified species of the found parasites and calculated the prevalence of infection with standard error of the mean.Results and discussion. We found representatives of the Coccidea and Kinetoplastea classes parasitizing in fish blood. Trypanoplasma acipenseris and Haemogregarina acipenseris were recorded in the Siberian sterlet. The pike was infected with T. schulmani and H. esoci. T. schulmani was found in the blood of the ide and roach. Piscicola geometra is the main host of flagellates and sporozoans that parasitize in fish blood in the basin of the Lower Irtysh. The roach and the Siberian sterlet become infected with parasitic flagellates from the age of 1+. All examined fish were infected in age groups 2+ – 4+. Haemogregarina parasitize in the pike aged 4+ and 5+, and in the Siberian sterlet aged 1+ – 4+ and 6+ – 7+.